Negotiation of Salafi Da’wah Discourse in Digital Space : An Islamic Communication Study of Rumaysho.com - Ali Ridho; Rusdiyanto; Mardan Umar; Mike Meiranti; Zainun Nur Hisyam Tahrus (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2026)
Digital transformation in religious communication has triggered significant changes in Islamic da’wah strategies and narratives, including among ideologically recognized groups such as Salafi. This study aims to examine how Salafi da’wah discourse is negotiated, adapted, and represented in digital spaces through Rumaysho.com, a popular da’wah platform managed by Ustaz Muhammad Abduh Tuasikal. Using a qualitative approach and Norman Fairclough’s Critical Discourse Analysis (CDA) method, this research analyzes 30 articles on creed (aqidah), worship (ibadah), and contemporary issues published between 2024 and mid 2025. The analysis follows Fairclough’s three dimensions, namely textual analysis, discourse practice, and social practice, to reveal how ideological messages are recontextualized to align with the participatory and plural characteristics of digital public spaces. The findings show that Rumaysho.com represents a shift in Salafi da’wah discourse, where textual orthodoxy is strategically adapted through communicative, aesthetic, and symbolic approaches, thereby maintaining ideological authority while reaching a broader public sphere. This study contributes a framework for understanding how theologically rigid groups strategically adapt their communicative repertoire in digital environments without doctrinal compromise.